2018
DOI: 10.3758/s13415-018-0603-7
|View full text |Cite
|
Sign up to set email alerts
|

Frontal delta-beta cross-frequency coupling in high and low social anxiety: An index of stress regulation?

Abstract: Cross-frequency coupling (CFC) between frontal delta (1–4 Hz) and beta (14–30 Hz) oscillations has been suggested as a candidate neural correlate of social anxiety disorder, a disorder characterized by fear and avoidance of social and performance situations. Prior studies have used amplitude-amplitude correlation (AAC) as a CFC measure and hypothesized it as a candidate neural mechanism of affective control. However, using this metric has yielded inconsistent results regarding the direction of CFC, and the fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 71 publications
11
45
0
Order By: Relevance
“…Thus, we speculate that a relatively higher delta-beta correlation among the positive shy children may then reflect an adaptive regulatory process. This finding and hypothesis is in line with previous work that has proposed that a relatively higher delta-beta correlation to be an adaptive neural correlate and converges with work finding this neural correlate to be linked with some adaptive psychosocial processes such as attentional control (Morillas-Romero et al, 2015;Putman et al, 2012) and low anxiety which is consistent in studies using a between-subject (Putman, 2011) and within-subjects measure of deltabeta correlation (Poppelaars et al, 2018).…”
Section: Frontal Delta-beta Correlationsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, we speculate that a relatively higher delta-beta correlation among the positive shy children may then reflect an adaptive regulatory process. This finding and hypothesis is in line with previous work that has proposed that a relatively higher delta-beta correlation to be an adaptive neural correlate and converges with work finding this neural correlate to be linked with some adaptive psychosocial processes such as attentional control (Morillas-Romero et al, 2015;Putman et al, 2012) and low anxiety which is consistent in studies using a between-subject (Putman, 2011) and within-subjects measure of deltabeta correlation (Poppelaars et al, 2018).…”
Section: Frontal Delta-beta Correlationsupporting
confidence: 92%
“…Another line of work has proposed that heightened delta-beta correlation may actually reflect an adaptive neural regulatory process, which has been supported in studies finding heightened delta-beta correlation in relation to increased attentional control (Morillas-Romero, Tortella-Feliu, Bornas, & Putman, 2015; Putman, Arias-Garcia, Pantazi, & van Schie, 2012) as well as lower levels of anxiety in adults (Poppelaars, Harrewijn, Westenberg, & van der Molen, 2018;Putman, 2011). This hypothesis is further supported by functional MRI studies that have found that the strength of cortico-subcortical coupling of the amygdala and frontal cortex is a correlate of emotion regulation efficiency (Banks, Eddy, Angstadt, Nathan, & Phan, 2007).…”
Section: Frontal Delta-beta Correlation and Affective Stylementioning
confidence: 93%
“…However, some have suggested that a within‐subject approach may provide further information regarding individual differences (e.g. Poppelaars, Harrewijn, Westenberg, & van der Molen, ; Schutter & Knyazev, ). A post hoc exploratory analyses using a within‐subject measure of frontal delta‐beta correlation yielded largely nonsignificant findings, with the exception of a trend ( p = .07) for the right frontal electrode in relation to social anxiety, with results mirroring our between‐subjects approach.…”
Section: Discussionmentioning
confidence: 99%
“…These predictors include (i) IQR of delta power for the prediction of IQR of FAA; (ii) IQR of beta power for the prediction of IQR of FTP; and (iii) IQR of FRP for the prediction of rFLBP. Although a concrete justification is hard, tight cross-frequency couplings among alpha, delta, and beta frequency bands, such as delta-alpha cross frequency coupling [35,36] and theta-beta coupling [37], might be reflected here.…”
Section: Resultsmentioning
confidence: 99%